Current status of stem cell treatments and innovative approaches for stress urinary incontinence - Seval, Mehmet Murat; Koyuncu, Kazibe (Frontiers in Medicine, 2022)
Stem cells are capable of self-renewal, differentiation, and the promotion of the release of chemokines and progenitor cells essential for tissue regeneration. Stem cells have the potential to develop into specialized cells if given the right conditions, to self-renew and maintain themselves, to generate a large number of new differentiated cells if injured, and to either generate new tissues or repair existing ones. In the last decade, it has become clear that treating lower urinary tract dysfunction with the patient's own adult stem cells is an effective, root-cause method. Regenerative medicine is predicated on the idea that a damaged rhabdosphincter can be repaired, leading to enhanced blood flow and improved function of the sphincter's exterior (striated) and internal (smooth) muscles. Stem cell therapy has the potential to cure stress urinary incontinence according to preclinical models. In contrast, stem cell treatment has not been licensed for routine clinical usage. This article reviews the current state of stem cell for stres urinary incontinence research and recommends future avenues to facilitate practical uses of this potential therapy modality.